Implementation of the Complex Adaptive System and Capability Approach in Poverty Alleviation in Coastal Communities in Takalar Regency - Adriana M; Gita Susanti (Journal Social Civilecial, 2025)
This study analyzes the implementation of coastal poverty alleviation policies in Takalar Regency, Indonesia, through the perspectives of Complex Adaptive System and Capability Approach. The research aims to examine how interactions among government institutions, local communities, and non-governmental organizations shape adaptive governance and influence the development of community capabilities in coastal areas. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving government agencies, village authorities, environmental organizations, fishermen, and seaweed farmers. The findings reveal that coastal poverty alleviation operates as an adaptive governance system characterized by dynamic actor interaction, feedback mechanisms, livelihood adaptation, and the emergence of community-based innovations. Poverty alleviation programs contribute not only to economic survival but also to the enhancement of practical reason, social affiliation, ecological awareness, and community resilience. However, unequal access to training, market dependency, and limited literacy continue to constrain capability expansion among coastal residents. The novelty of this study lies in integrating Complex Adaptive System and Capability Approach perspectives to explain coastal poverty alleviation as both an adaptive institutional process and a multidimensional capability development process. The study provides theoretical and practical insights for developing adaptive, participatory, and capability-oriented coastal governance policies.